Generation and Neuronal Differentiation of hiPSCs From Patients With Myotonic Dystrophy Type 2 - Spitalieri, Paola; Talarico, Rosa V.; Murdocca, Michela; Fontana, Luana; Marcaurelio, Marzia; Campione, Elena; Massa, Roberto; Meola, Giovanni; Serafino, Annalucia; Novelli, Giuseppe; Sangiuolo, Federica; Botta, Annalisa (Frontiers in Physiology, 2018)
Human induced pluripotent stem cells (hiPSCs)-patient specific are an innovative tool to reproduce a model of disease in vitro and summarize the pathological phenotype and the disease etiopathology. Myotonic dystrophy type 2 (DM2) is caused by an unstable (CCTG)n expansion in intron 1 of the CNBP gene, leading to a progressive multisystemic disease with muscle, heart and central nervous dysfunctions. The pathogenesis of CNS involvement in DM2 is poorly understood since no cellular or animal models fully recapitulate the molecular and clinical neurodegenerative phenotype of patients. In this study, we generated for the first time, two DM2 and two wild type hiPSC lines from dermal fibroblasts by polycistronic lentiviral vector (hSTEMCCA-loxP) expressing OCT4, SOX2, KLF4, and cMYC genes and containing loxP-sites, excisable by Cre recombinase. Specific morphological, molecular and immunocytochemical markers have confirmed the stemness of DM2 and wild type-derived hiPSCs. These cells are able to differentiate into neuronal population (NP) expressing tissue specific markers. hiPSCs-derived NP cells maintain (CCTG)n repeat expansion and intranuclear RNA foci exhibiting sequestration of MBNL1 protein, which are pathognomonic of the disease. DM2 hiPSCs represent an important tool for the study of CNS pathogenesis in patients, opening new perspectives for the development of cell-based therapies in the field of personalized medicine and drug screening.